IMPLEMENTASI MODERASI BERAGAMA DI DESA KADEMANGAN, KECAMATAN SURADE, KAB. SUKABUMI - Husaeni, Firman (STISIP Widyapuri Mandiri Sukabumi, 2025)
This study aims to explore the implementation of religious moderation in Kademangan Village, Surade District, Sukabumi Regency, particularly in the context of a community coexisting with an anti-loudspeaker Islamic boarding school (pesantren). Religious moderation, which includes attitudes of tolerance and openness in practicing religion, plays an important role in maintaining harmony and social cohesion in a heterogeneous society. This study employs a qualitative method to analyze how religious moderation is applied and the challenges faced by the community in interacting with the anti-loudspeaker pesantren, which has an exclusive approach to religious teachings. The results indicate that although significant efforts have been made to implement religious moderation through dialogue and joint social activities, major challenges remain due to the pesantren's exclusive stance and the lack of understanding of religious moderation among some members of the community. This study offers recommendations to enhance the effectiveness of religious moderation and improve relations between the community and the anti-loudspeaker pesantren.